Analisis Pengaruh Struktur Kepemilikan, Ukuran dan Pertumbuhan Perusahaan terhadap Manajemen Laba pada Perusahaan BEI Tahun 2014-2018 - Mardianto Mardianto (Pusat P2M Politeknik Negeri Batam, 2020)
The study was conducted with the aim of analyzing the effect of ownership structure, company size and company growth as an independent variables on earnings management as the dependent variable. Ownership structure is represented by proxies of ownership concentration, institutional ownership, family ownership, and state ownership. This study collected data with a purposive sampling method. The object of collecting data samples is in the form of data from financial reports and annual reports of companies listed on the Indonesia Stock Exchange (IDX) from 2014 to 2018. This study uses multiple regression analysis methods to examine the effect of independent variables on the dependent variable. Research data were tested using Statistical Product and Service Solutions (SPSS). The results showed that family ownership, institutional ownership and state ownership had a significant positive effect on earnings management. Ownership concentration has a significant negative effect on earnings management. Meanwhile, company size and company growth do not have a significant relationship with earnings management.